The art and science of connection : why social health is the missing key to living longer, healthier, and happier - Killam, Kasley (HarperOne, an imprint of HarperCollinsPublishers, 2024)
In this groundbreaking redefinition of health and wellbeing, an internationally recognized expert in social health argues that the definition of wellbeing is missing a major component: social connection, proving that relationships not only make us happy, but they are also critical to our overall health and longevity.